IMPROVE DATA ENCRYPTION BY USING DIFFIE-HELLMAN AND DNA ALGORITHMS, AUTHENTICATED BY HMAC-HASH256 - Mustafa, Nada Abdul Aziz (International journal of advanced research in computer science, 2025)
: The need for means of transmitting data in a confidential and secure manner has become one of the most important subjects in the world of communications. Therefore, the search began for what would achieve not only the confidentiality of information sent through means of communication, but also high speed of transmission and minimal energy consumption, Thus, the encryption technology using DNA was developed which fulfills all these requirements [1]. The system proposes to achieve high protection of data sent over the Internet by applying the following objectives: 1. The message is encrypted using one of the DNA methods with a key generated by the Diffie-Hellman Ephemeral algorithm, part of this key is secret and this makes the process of predicting the key very difficult. 2. Ensuring the integrity and reliability of the transmitted data using the HMAC-HASH256 algorithm that is resistant to attacks, where the 256 hash function is used with a key generated from the Diffie-Hellman Ephemeral algorithm. 3. Analyzing the system by trying to measuring the impact of using encryption with authentication on cost and speed and calculating the time taken to implement the HMAC-SHA256 algorithm. System implementation was done by using IntelliJ IDEA with java FX.